An Analisys Of Students’ Ability In Writing Analytical Exposition Text - Dewi Kristiani Bawamenewi; Elda Martha Suri; Widya Juli Astria (Kilau Publishing, 2025)
This research aims to analyze and describe the overall ability of eleventh-grade students in writing analytical exposition text and specifically to identify their most significant difficulties across the five components of writing: Content, Organization, Vocabulary, Grammar, and Mechanics. The design of this research is descriptive research. The sample consisted of 30 students from eleventh-grade AKL 1 at SMK Negeri 2 Padang, selected using purposive sampling. The primary instrument for data collection was a writing test, and the results were analyzed using the scoring rubric for writing test to determine the students’ average score and their proficiency level for each component. The research found that the students' overall writing ability fell into the good category, achieving an average score of 78. Students performed well in the components of Content, Organization, and Mechanics. However, the analysis revealed that their most critical difficulty was in the Vocabulary component, which significantly affected the accuracy and richness of their language use in conveying complex ideas. In conclusion, the students’ ability in writing analytical exposition text is at a moderate-to-good level. The primary constraint hindering higher proficiency is the lack of vocabulary mastery.